A Unique Case of Aggressive Central Giant Cell Granuloma in a 10-Year-Old Boy With 16p13.11 Microdeletion Syndrome - Betty J. Shum MD; Mimi S. Kim MD, MSc; Katelyn Kondra MD; Jeffrey A. Hammoudeh MD, DDS, FACS; Charles Strom MD; Anna Ryabets-Lienhard DO (SAGE Publishing, 2022)
Central giant cell granuloma (CGCG) is a rare disease characterized by sporadic, benign, intraosseous mandibular lesions of unknown etiology. Histologically, these lesions are indistinguishable from brown tumors of hyperparathyroidism and cherubism, and occasionally have been associated with different syndromes raising a question for genetic etiology. The CGCG has varied presentation ranging from nonaggressive and indolent to aggressive, destructive, and recurrent, often posing diagnostic and therapeutic challenges. Herein, we present the first case of a 10-year-old boy with CGCG and 16p13.11 microdeletion syndrome, highlight the diagnostic challenges inherent to this heterogeneous disorder, and discuss the genetics and treatment approaches of these complex lesions.